Weak Ties on Old Roads: Inscribed Stopping-Places and Complex Networks in the Eastern Desert of Graeco-Roman Egypt - Hackley Laurel Darcy; Gates-Foster Jennifer; Redon Bérangère (Open Archaeology)
This article argues that the landscape attributes of a network are an influential factor in the network’s formation and function. By this, we mean that the realities of terrain and environment affect both physical and social networks in ways that can be productively incorporated into network analyses. Using two case studies from the sites of Buweib and the Paneion of the Wadi Minayh in the Eastern Desert of Egypt, we illustrate how landscape performs as an actor in the networks of the Graeco-Roman period, influencing the location of network “weak-tie” nodes and functioning as a medium of communication that, through practices of landscape marking, allows information to be exchanged between travelers, across language and cultural barriers, and even across millennia. These inscribed stopping places act as vibrant spaces of exchange in the desert by exercising an influence on how people interact physically and conceptually with the landscape.